A Triple‐Gradient Host for Long Cycling Lithium Metal Anodes at Ultrahigh Current Density. Issue 30 (22nd June 2020) - Le, TrungHieu; Liang, Qinghua; Chen, Ming; Yang, Ciqing; Yu, Zhihao; Cheng, Jie; Kang, Feiyu; Yang, Ying
Abstract: The viable Li metal anodes (LMAs) are still hampered by the safety concerns resulting from fast Li dendrite growth and huge volume expansion during cycling. Herein, carbon nanofiber matrix anchored with MgZnO nanoparticles (MgZnO/CNF) is developed as a flexible triple‐gradient host for long cycling LMAs. The superlithiophilic MgZnO nanoparticles significantly increase the wettability of CNF for fast and homogeneous infusion with molten Li. The in‐built potential and lithiophilic gradients constructed after an in situ lithiation of MgZnO and CNF enable nearly zero Li nucleation overpotential and homogeneous deposition of lithium at different scales. As such, the LMAs based on MgZnO/CNF achieve long cycling life and small overpotential even at a record‐high current density of 50 mA cm −2 and a high areal capacity of 10 mAh cm −2 . A full cell paring with this designed LMA and LiFePO4 exhibits a capacity retention up to 82% after 600 cycles at a high rate of 5 C. A Li‐ion capacitor also shows an impressive capacity retention of 84% at 5 A g −1 after 10 000 cycles. Such a Li@MgZnO/CNF anode is a promising candidate for Li‐metal energy storage systems, especially working under ultrahigh current density. Abstract : A carbon nanofiber matrix anchored with MgZnO nanoparticles is designed as a triple‐gradient host for Li metal anodes. Because of the coupling effects of lithiophilicity gradient, nucleation overpotential gradient, and conductivity gradient, the molten lithium infusion or Li‐ion deposition would be facilitated in a controllable way, which helps in achieving long lifespans under an ultrahigh current density of 50 mA cm −2 .